Faktor-Faktor Yang Mempengaruhi Efektivitas Pelayanan Sistem Resi Gudang (Srg) Dan Manfaatnya Kepada Petani Padi ( Kasus di Kecamatan Warungkondang, Kabupaten Cianjur, Jawa barat ) - Ilham Maulana Yusuf; Euis Dasipah; Karyana KS (Paspalum: Jurnal Ilmiah Pertanian, 2022)
This research aims to find out the factors that affect the service function of warehouse receipt system (SRG) and its benefits to farmers. Theanalysis is the farmer  utilizing SRG services. The technique of determining respondents is done from the withdrawal of examples with a simple random technique, The sample size using the Slovin formula was obtained by 60 people. Hypothesis testing analysis techniques used multiple linear regression analysis and chisquare. The results of the research obtained by Fator-factors that affect the service function of The Warehouse Receipt System (SRG) to farmers in Warungkondang District, Cianjur Regency are: land area, harvest area, land productivity, dependence on marketing agencies, capital, and the effectiveness of HPP (Government Purchase Price) policy.   The achievement rate is 78.75%.  SRG Service functions to farmers include: storage, grain quality test; delivery of goods, supervision, and cooperation. The achievement rate was 77.33%.  The benefits of SRG in order to provide services to farmers include: better price / higher, product quality, quantity of products, and financingguarantees.   The achievement rate is 69.06%.  Factors that have a real effect on the function of SRG services are: land area, harvest area, land productivity, and capital, while the effect is not real, namely: dependence on capital release, and HPP policy.  The function of SRG services has a positive effect on the benefits obtained by farmers. With the understanding of the better the running of the SRG function, the better it will provide the benefits obtained by farmers.